2019
DOI: 10.18632/aging.101943
|View full text |Cite
|
Sign up to set email alerts
|

Laminin α4 overexpression in the anterior lens capsule may contribute to the senescence of human lens epithelial cells in age-related cataract

Abstract: Senescence is a leading cause of age-related cataract (ARC). The current study indicated that the senescence-associated protein, p53, total laminin (LM), LMα4, and transforming growth factor-beta1 (TGF-β1) in the cataractous anterior lens capsules (ALCs) increase with the grades of ARC. In cataractous ALCs, patient age, total LM, LMα4, TGF-β1, were all positively correlated with p53. In lens epithelial cell (HLE B-3) senescence models, matrix metalloproteinase-9 (MMP-9) alleviated senescence by decreasing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 98 publications
1
18
0
Order By: Relevance
“…Our transcriptome results also allowed us to identify and verify some genes rarely associated with ARC. Yan et al found that the increased expression of laminin α4 in the anterior lens capsule is the main mechanism leading to the occurrence of ARC [16], which is consistent with our transcriptome sequencing results. Moreover, the inhibition of NLRP3 was shown to reduce oxidative stress-induced damage to human lens epithelial cells, while NLRP3 protein expression was significantly increased in lens epithelial cells under oxidative stress [17], which was also consistent with our verification results.…”
Section: Discussionsupporting
confidence: 92%
“…Our transcriptome results also allowed us to identify and verify some genes rarely associated with ARC. Yan et al found that the increased expression of laminin α4 in the anterior lens capsule is the main mechanism leading to the occurrence of ARC [16], which is consistent with our transcriptome sequencing results. Moreover, the inhibition of NLRP3 was shown to reduce oxidative stress-induced damage to human lens epithelial cells, while NLRP3 protein expression was significantly increased in lens epithelial cells under oxidative stress [17], which was also consistent with our verification results.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, as the lifespan increases, age-related dysfunction, such as ARC, has become a growing public health issue [26] . Senescence of LECs has been documented involved in the occurrence and the development of ARC [5] . Our results showed that the LECs in the naturally aged mice (Aged) were at, arranged unevenly and the density of LECs decreased markedly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The normal construction and function of LECs is essential for the maintenance of the transparency and metabolic homeostasis of the entire lens [3] . Accumulating evidence indicate that the senescence of LECs could cause modi cation, denaturation, aggregation of lens proteins including enzyme and crystallins, thereby ultimately leading to lens opaci cation or even cataract [3][4][5] . Cataract, especially age-related cataract (ARC), remains the leading cause of visional disability and blindness, which severely affects the quality of life of elderly individuals [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture HLE B-3 stable cell line was obtained from theAmericanTypeCulture Collection (Manassas, VA, USA) and culturedaspreviouslydescribed [28,29].…”
Section: Single Strand Conformation Polymorphism(sscp)andsequencingmentioning
confidence: 99%
“…The plasmids of blank vector [pcDNA3.1(+)], wildtypeCRYAA(CRYAA-WT) and CRYAA-E83E were obtained fromBSgensCompany(Harbin, China). HLE B-3 cells were seeded in 6-wellplatesandwere transfected with 2 µg/well pcDNA3.1(+),CRYAA-WTandCRYAA-E83E plasmids using Invitrogen Lipofectamine®2000Reagent(Thermo Fisher Scienti c Inc., Shanghai, China)asdescribedpreviously [28,29].…”
Section: Plasmid Transfectionmentioning
confidence: 99%